Acute Decompensation of Noncommunicating Hydrocephalus Caused by Dilated Virchow-Robin Spaces Type III in a Woman Treated by Endoscopic Third Ventriculostomy: A Case Report and Review of the Literature - Ottenhausen, Malte; Meier, Ullrich; Tittel, Anja; Lemcke, Johannes (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background and Importance Even though dilated Virchow-Robin spaces (VRS) are a very rare entity, they can compel the clinician to start immediate intervention in the case of acute onset of symptoms. To allow a well-balanced management decision, we compiled a summary of all cases published in the literature and discuss the different methods and indications for neurosurgical intervention in relation to dilated VRS.Clinical Presentation We report a case of a 43-year-old female patient who came to admission after syncope with a history of unspecific neck pain, fatigue, diplopia, and dizziness. Dilated VRS type III causing a noncommunicating hydrocephalus were found to be responsible. Although the patient was initially awake, within 72 hours after admission, a deterioration of consciousness and repeated vomiting were observed. The patient underwent an urgent endoscopic third ventriculostomy (ETV) and was discharged in a good condition.Conclusion To the best of our knowledge, the case presented here is the first case of acute decompensation of a noncommunicating hydrocephalus caused by dilated VRS. Neurosurgical intervention is required in cases of noncommunicating hydrocephalus caused by giant tumefactive VRS. The treatment options are mono- or biventricular shunt surgery or ETV. Because ETV provides the possibility of cyst fenestration and membrane sampling, it appears to be the most advantageous treatment option.
Keywords: hydrocephalus; Virchow-Robin spaces; ETV